Exploration of the mechanism of cavitation vortex rope and vortex development in the draft tube of tubular turbine units - Cheng, Chuang; Li, Zhenggui; Shen, Changrong; Gu, Shenglong; Zeng, Chuchu; Bai, Chuanzheng; Liu, Meng; Hu, Junfeng (International Journal of Agricultural and Biological Engineering, 2024)
Draft tube vortex rope is considered a special cavitation flow phenomenon in tubular turbine units. Cavitation vortex rope is one of the most detrimental factors affecting the safety of hydraulic turbines. In this study, ANSYS CFX software was utilized to numerically simulate the internal cavitation flow of a hydraulic turbine draft tube. The evolution of the cavitation vortex core was characterized by vortex line distribution and vorticity transport equation. The shape and number of blades influenced the revolving direction and distribution characteristics of the vortex close to the runner cone, which formed a counterclockwise-clockwise-counterclockwise distribution pattern. Simultaneously, there were many secondary flows in the draft tube. Mutual cancellation and dissipation between the flows was one of the reasons for reduction in vorticity. When the cross-sectional shape of the draft tube was changed, the vorticity was distributed from the center of the vortex rope to all parts of the cross-sectional draft tube, with extreme values at the center and at the walls. The vortex stretching and dilatation terms played a major role in the change in vorticity, with the baroclinic torque having an effect at the center of the vortex rope, this study is helpful to understand the flow of water in the draft tube and guide the design and optimization of the draft tube in engineering application. Keywords: cavitation, vortex rope, vorticity transport equation, vortex line, draft tube DOI: 10.25165/j.ijabe.20241701.8143 Citation: Cheng C, Li Z G, Shen C R, Gu S L, Zeng C C, Bai C Z, et al. Exploration of the mechanism of cavitation vortex rope and vortex development in the draft tube of tubular turbine units. Int J Agric & Biol Eng, 2024; 17(1): 163-171.